Longitudinal trends and predictors of limitations in activities of daily living in community-dwelling older adults: evidence from the KLoSA study - Oh, Eunmi; Moon, SeolHwa; Hong, Gwi-Ryung Son (Frontiers in Public Health, 2024)
BackgroundAs life expectancy increases, the number of older adults with functional limitations is also increasing. Functional limitations are associated with adverse health outcomes such as reduced independence, diminished quality of life (QoL), and disability. Therefore, identifying which activities of daily living (ADLs) are limiting and understanding the influencing factors are crucial for developing tailored interventions. Although various factors influence ADL limitations, few studies have identified the longitudinal factors associated with each ADL. This study explores the longitudinal trends and factors associated with the ADL total score and functional limitations with each ADL among older adults in Korea.MethodsUsing data from the Korean Longitudinal Study of Aging (KLoSA) from 2006 to 2020, we analyzed 1,388 people aged 65 and older who had no ADL limitations in 2006. An ADL limitation was defined as partial or complete dependence in any of the following ADLs: getting dressed, washing face and hands, bathing, eating, transferring, toileting, and continence. We used repeated measures analysis of variance and multivariate logistic regression to investigate the trends and predictors of ADL limitations over a 14-year period.ResultsIn 2006, the mean age of the participants was 69.88 years (SD = ±4.11), and 60.20% were female. The prevalence of total ADL limitations and limitations in each of the seven ADLs increased gradually during the 14 years of follow up. In 2020, the ADL items with the highest prevalence of limitations were bathing, getting dressed, and washing face and hands. The common significant predictors for total ADL limitations and limitation in the top three ADLs were age and cognitive function.ConclusionADL limitations among Korean older adults significantly increase over time, which highlights the need for integrated early intervention and continuous support for bathing limitations, including the application of integrated assistive technologies. In particular, because age and cognitive function were identified as the major predictors for limitations in both total ADLs and the top three ADLs, early assessment and appropriate intervention strategies need to consider those factors to prevent ADL limitations in older adults or to meet the immediate needs of those already experiencing ADL limitations. This approach could enhance the QoL for older adults and contribute to the development of long-term healthcare plans.